Sulfoximine substituted quinazolines for pharmaceutical compositions US 20150005278 (A1): a patent evaluation. (2nd August 2016) - Gopaul, Kaalin; Koorbanally, Neil A.
ABSTRACT: Mnk1 and Mnk2 are protein kinases responsible for phosphorylating eIF4E, a eukaryotic initiation factor responsible for initiating translation. Inhibiting Mnk1 and Mnk2 could therefore play a role in treating metabolic diseases such as cancer, diabetes, and hyperlipidemia. A wide range of sulfoximine substituted quinazolines were synthesised and evaluated for their Mnk1 and Mnk2 inhibitory activity. Amongst these compounds, 26 quinazolines showed activity against Mnk1 at <100 nM and 54 showed activity against Mnk2 at 1 nM. The results indicate that this scaffold is much more active against Mnk2 than Mnk1. The synthesised compounds may be future drugs in the treatment of metabolic diseases.